2013
DOI: 10.1371/journal.pone.0067801
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis of Zebrafish Melanocytes, Iridophores, and Retinal Pigmented Epithelium Reveals Indicators of Biological Function and Developmental Origin

Abstract: In order to facilitate understanding of pigment cell biology, we developed a method to concomitantly purify melanocytes, iridophores, and retinal pigmented epithelium from zebrafish, and analyzed their transcriptomes. Comparing expression data from these cell types and whole embryos allowed us to reveal gene expression co-enrichment in melanocytes and retinal pigmented epithelium, as well as in melanocytes and iridophores. We found 214 genes co-enriched in melanocytes and retinal pigmented epithelium, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
108
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 107 publications
6
108
2
Order By: Relevance
“…The expression of cx39.4 in melanophores was independently reported by the Johnson group (52). Cx39.4 expression was detected by the transcriptome analysis of melanophores using NGS (next-generation sequencing) (52). Our RT-PCR results and transgenic experiments also suggested the expression of Cx39.4 in pigment cells.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The expression of cx39.4 in melanophores was independently reported by the Johnson group (52). Cx39.4 expression was detected by the transcriptome analysis of melanophores using NGS (next-generation sequencing) (52). Our RT-PCR results and transgenic experiments also suggested the expression of Cx39.4 in pigment cells.…”
Section: Discussionsupporting
confidence: 73%
“…Recently, Irion et al (36) successfully showed that Cx39.4 is also involved in skin pattern formation and that Cx39.4 functions in melanophores and xanthophores. The expression of cx39.4 in melanophores was independently reported by the Johnson group (52). Cx39.4 expression was detected by the transcriptome analysis of melanophores using NGS (next-generation sequencing) (52).…”
Section: Discussionmentioning
confidence: 99%
“…Higdon and Johnson showed by RNA-seq that mpv17 is highly enriched in iridophores compared to other pigment cells such as melanocytes (Higdon et al, 2013). Krauss, et al, also recently noted that zebrafish mpv17 also localizes to the mitochondria, similar the the human and mouse protein.…”
Section: Resultsmentioning
confidence: 99%
“…In zebrafish, an attempt to find overlapping transcriptional signature between melanophores and iridophores identified 62 genes with similar expression patterns in both chromatophores, but igsf11 and pmel were not among them (Higdon, Mitra & Johnson, 2013). However, the study was done using larval melanophores and iridophores from the body and not from the fins (Higdon, Mitra & Johnson, 2013).…”
Section: Discussionmentioning
confidence: 99%